Gaining Supply Chain Resilience and Performance Sustainability through Supply Chain Agility in Furniture SMEs in Yogyakarta - Pratondo, Katon; Kusmantini, Titik; Sabihaini, Sabihaini (International Journal of Social Science and Business, 2021)
The COVID-19 pandemic has disrupted many activities throughout the supply chain, from supplying unrefined materials to a product being consumed by consumers. More than five million companies have been undermined by the COVID-19 pandemic, several companies have also temporarily closed stores, cancelled orders, and suspended production. Therefore, this study aims to evaluate and examine the role of supply chain agility on supply chain resilience and supply chain performance sustainability. This study uses a quantitative method with the Smart PLS version 3.3.3 analysis tool and also involves 54 furniture SMEs in the Special Region of Yogyakarta as respondents. The results of this study find and prove that supply chain agility has a positive and significant effect on supply chain resilience and supply chain performance sustainability.